Wind Energy Density Calculation Based on Different Data SourcesA Comparative Study for Al-Shehabi Site-Iraq - Oudah, Samah Shyaa; abduallh, Yahya basheer; Hadi, Firas A. (Iraqi Journal of Science, 2024)
This research proposed a 5.0 MW wind power project at the Al-Shihabi site in Iraq. The wind speed was collected from the Al-Shehabi metrological station at heights 10, 30, 50, and 52 m with 10-minute time intervals; then those data were compared with the hourly wind speed measured at 50 m for one year above the ground level obtained from the NASA site. The data were modeled using the Weibull distribution function for all wind power heights. Three methods were used to estimate Weibull parameters: Maximum Likelihood, Least Squares, and WAsP, which were executed to determine the numerical values of Weibull shape parameter (k), scale parameter (c), and mean wind speed. It is concluded that the annual mean wind speeds and the annual mean wind power densities of the measured data at 10, 30, 50, and 52 m heights were 4.607m/s, 144.0W/m2, 6.068 m/s, 257.0 W/m2, 6.673m/s, 346.0 W/m2, 6.91m/s, 359.0W/m2 respectively, as 3rd class (Gentle Breeze), while the results of wind data from NASA at 50 m were 5.241m/s and 126 W/m2 as 2nd (Light breeze). The predicted power density was analyzed using ten wind energy system models of rated capacity 10, 25, 50, 60, 100, 330, 500, 850, and 900 kW.